FAMILY AS A SOCIAL GROUP AND A SOCIAL INSTITUTION (American Journal of Research in Humanities and Social Sciences, 2024)
Time goes on, the topic of families, for one reason or another, initially without a child, increasingly acquires, and is associated with the theoretical uncertainty of the scientific status of this type of family structure, as well as the applied significance of research in this area.